2011
DOI: 10.1111/j.1467-6419.2011.00697.x
|View full text |Cite
|
Sign up to set email alerts
|

Government Size and Growth: A Survey and Interpretation of the Evidence

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
116
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(124 citation statements)
references
References 83 publications
7
116
1
Order By: Relevance
“…Depending on methods used and on countries studied, the obtained results are highly contradictory. However, as pointed out by Bergh and Henrekson (2011), focusing on OECD countries and relying on panel data estimations reveals a more consistent picture. Correlation between government size and economic growth is negative and the sign seems not to be an unintended consequence of reverse causality.…”
Section: Direct Effects Of Fiscal Policy On Tfpmentioning
confidence: 99%
“…Depending on methods used and on countries studied, the obtained results are highly contradictory. However, as pointed out by Bergh and Henrekson (2011), focusing on OECD countries and relying on panel data estimations reveals a more consistent picture. Correlation between government size and economic growth is negative and the sign seems not to be an unintended consequence of reverse causality.…”
Section: Direct Effects Of Fiscal Policy On Tfpmentioning
confidence: 99%
“…There is a vast empirical literature investigating the relationship between the size of the government and economic growth (see Slemrod, 1995;Myles 2009;Bergh and Henrekson, 2011 for overviews). A review by Bergh and Henrekson (2011), based on papers published in peer reviewed journals after 2000, suggested a negative relationship in OECD countries. Likewise, a recent OECD study confirmed a negative relationship between the size of government and GDP growth (Fall and Fournier, 2015).…”
Section: Public Spending and Economic Growthmentioning
confidence: 99%
“…At low levels of income, there is a positive association between government size and growth, if the government is successful in collecting taxes and providing the basic functions necessary for economic growth such as protecting property rights and enforcing the rule of law (Slemrod, 1995;Bergh and Henrekson, 2011). Moreover, when such a minimal government expands its activities to provide infrastructure, health care and education, the effect on growth is likely positive.…”
mentioning
confidence: 99%
“…Recent studies, exploiting cross-country panel data and including a wider range of control variables, provide better insights on the link between the size of the government and growth. A review by Bergh and Henrekson (2011), based on papers published in peer reviewed journals after 2000, suggested a negative relationship in OECD countries. Likewise, a recent OECD study also found a negative relationship between the size of government and GDP growth in a sample of OECD countries (Fall and Fournier, 2015).…”
mentioning
confidence: 99%